The Effect of Self Efficacy and Attitudes on Nurses' Preparedness in Facing Earthquake Disasters - Ida, Ida; Sanjaya, Waqid; Permana, Iwan; La Ede, Abdul Rahman (Indonesian Journal of Global Health Research, 2025)
Indonesia is classified as a country with a high level of natural disaster vulnerability, including volcanic eruptions, tsunamis, banji, landslides, earthquakes and so on. One important step in reducing the risk of natural disasters is to improve preparedness for individuals and health workers. Preparedness can be influenced by various factors including self efficacy and attitude. The purpose of this study was to determine the effect of self efficacy and attitude on nurses' preparedness in facing earthquake disasters in the Coastal Region of Sukabumi Regency. Methods: Correlational research with cross sectional approach. The population and sample in this study were all nurses in the Coastal Region of Sukabumi Regency as many as 160 people, using total sampling technique. Data collection techniques using questionnaires. The validity test results on all instruments for each variable have a p value < 0.05 and are declared valid. The results of the instrument reliability test for each variable > 0.6 so that it is declared to have a high reliability value. Data analysis included univariate analysis using mean and standard deviation, bivariate analysis using simple linear regression and multivariate analysis using multiple linear regression. Results: The results showed that there was a significant effect of self efficacy (p-value 0.017) and attitude (p-value 0.000) on nurse preparedness. There is a simultaneous influence of self efficacy and attitude towards nurse preparedness which is quite strong (R Square 0.274). Conclusion: There is a significant effect of self efficacy and attitude on nurse preparedness.